RICE SUPPLY CHAIN PERFORMANCE ANALYSIS USING THE SUPPLY CHAIN OPERATIONAL REFERENCE (SCOR) APPROACH - Dwi Apriyani; Octaviana Helbawanti; Keumala Fadhiela ND (Journal of Agri Socio Economics and Business, 2022)
Supply chain performance measurement is conducted to evaluate the goal achievement organization and determine its position towards competitors. This study aimed to analyze the supply chain performance of rice at the farmer level using Supply Chain Operational Reference (SCOR). This study is conducted using a case study approach and purposive sampling to locate. Analyze methods using calculation of performance score in every indicator of SCOR attributes, and then the result will be compared to superior card score. Comparing results will indicate the score of parity, advantage, or superior. Results showed that some performance in supply chain activities is not optimal yet, so it has to be fixed. Activities that need to fix to reach a superior score are order fulfilment, order fulfilment cycles, cash to cash cycle time, daily stock, and total supply chain cost. We recommend that MDP Company needs to increase the volume of grains absorbed by farmer partners by adding market targets to push assets flow. The farmers had to reduce moreover remove activities that impacted increasing supply chain costs. In addition, it needs accompaniment from MDP Company to the farmer's partner, especially at post-harvest management, in order to increase the quality of milling raw material and pass the market qualification.